Strand 3: Human Tortoises on the Net: Taking Account of Learning Speed in Designing Networked Learning for Adults - Wiltsher, Chris (Proceedings of the International Conference on Networked Learning, 1998)
Human learning takes time. By examining the processes of human learning we see that formal learning programmes muse provide time for learning to take place, particularly where adults are concerned. Traditional methods of delivering learning material, face to face and at a distance, have time for learning built into them, but networked learning methods do not. The speed and volume of information available by networked means make learning more difficult, since compared with machines, human beings are very slow at information processing. However, chose who are experts in a field can be shown to learn at different speeds from chose who are novices. Reviewing the reasons for this difference leads co suggestions about how time for learning can be provided in networked learning for continuing professional development, thereby enhancing learning.